Customers' acceptance of artificially intelligent service robots: The influence of trust and culture. (June 2023) - Chi, Oscar Hengxuan; Chi, Christina G.; Gursoy, Dogan; Nunkoo, Robin
Abstract: This study addresses two critical research gaps in human-robot interaction (HRI): the limited systematic research on the role of trust in customers' acceptance of artificially intelligent (AI) robots; and the lack of understanding of robot acceptance under different cultural backgrounds. Drawing on the AIDUA framework, this study examines the impacts of trust and moderating effects of both national (the U.S. and China) and individual culture on customers' intentions to use AI robots in hospitality services by developing a theoretical model. The model is tested on data collected using online data collection platforms from 491 U.S. and 495 Chinese respondents. PLS-SEM and the bootstrapping method were used to test the hypothesized relationships and analyze the moderating effects of culture, respectively. The findings suggest that trust in interaction with AI robots is a significant higher-order construct that influences the intention of use. Furthermore, uncertainty avoidance, long-term orientation, and power distance have been found to exhibit significant moderation effects. The results of this study extend the theoretical frameworks in HRI and provide detailed guidance to promote AI robot applications across different cultures. Highlights: Examine the impacts of trust and culture on the acceptance of hospitality robots. Suggest that trust is a significant high-order construct that influences intention. Several cultural dimensions have been found to exhibit moderation effects. Provide guidance of AI application in different national cultures. Identify how individuals' cultural values influence the use of hospitality robots.